Translation as a Bridge between the East and the West in Ahdaf Soueif’s Hybrid Novel The Map of Love (1999) - Mohammedi, Khadra; GUELLIL ,Assia (Faculty of Letters and Foreign Languages Department of English, 2018)
The present study deals with the issue of translation that has recently become a crucial subject in postcolonial literature. It examines Ahdaf Soueif’s The MAP of Love to highlight the role of translation as bridge between the Egyptian culture and the British culture as well as between the East and The West and thus reshape a cultural identity. Therefore, this study begins with a brief theoretical overview on postcolonial literature and translation as a key concept in postcolonial theory to stress on the fact that The Map of Love is a postcolonial novel with hybrid text and hybrid characters. However, the main focus will be on analyzing the notion of translation in text, context as well as characters. At the end, the study comes out to the conclusion that translation has a big role in bridging between cultures and bringing them together in mutual tolerance and understanding